Science Lecturers’ Seeming Use of Google Classroom for Instruction - Onojah Amos Ochayi; Obielodan Omotayo Olabo; Onojah Adenike Aderogba; Abdulrahman Mohammed Rabiu; Akpeji Peace (ASEAN Journal of Science and Engineering Education, 2021)
This study investigated the science lecturers’ perceived use of Google classroom for instruction as well as the influence of teaching experience and experience in the use of the google classroom for instruction. The study hires a survey method with the use of the online questionnaire. All lecturers in the faculty of science made up the population for the study. The findings established that science lecturers have good seeming on the use of google classroom for instruction. Also, lecturers’ years of experience influenced their use of Google classroom for instruction. The study concluded that lecturers perceived use of google classroom encouraged them to use it in their instructional activities. It was however recommended that Google Classroom also has to constantly upgrade to suit user needs so as not to be replaced with newer, better, faster, more efficient alternatives.